Applications of Geographical Information System (GIS) in Assessment of Water Balance in Watersheds - Cholke, SP (International Journal of Computer Sciences and Engineering, 2025)
The present study area is lying in the drought-prone zone of North Ahmednagar district, where the Bhandardara dam is main source of water for drinking, agriculture, and industries. Last 10 to 15 years mainly because of an extra share of water is taking by industries and urban centers, numbers of villages are facing water scarcity problem.GIS a powerful technique can be utilized to determine the water balance in watersheds. Therefore, in present study emphasis has been given to the scientific investigation of water balance within eight watersheds covering areas of three tehsils namely, Rahata, Shrirampur and Nevasa using GIS technique. The result indicates that total demand for water is 195.52 MCL, whereas water available is 1253.30 MCL consequently, 1057.77 MCL water is surplus in the entire study area. Though the 1057.77 MCL water is surplus in all eight sub-watersheds, water scarcity is increasing day by day. The result clearly shows that miss management of water in this area is the main cause of water scarcity hence, it needs to the hour that to focus on water management with storing the surplus water and its proper utilization. The modification of agricultural practices and changes in irrigation schemes are the most crucial steps should be taken to eliminate the miss management of water. With the help of GIS technique, it is possible to tackle the water scarcity problem in watersheds.